English Students’ Perception Towards the Use of YouTube as a Learning Resource to Enhance English Speaking Skills: A Case Study at the Third Semester of the English Education Program, University of Mataram - Octaviani, Nurul; Fitriana, Eka; Putera, Lalu Jaswadi (Journal of English Education Forum (JEEF), 2025)
This study discusses the perceptions of third-semester students in the English education program at Mataram University regarding the utilization of YouTube as a learning resource for enhancing their English-speaking skills. This study aims to investigate and determine students' perceptions of YouTube as a learning resource to improve their English-speaking skills and the factors that influence them. The research methods used in this study are mixed methods by distributing questionnaires and conducting interviews. The results of this study show that students have a positive view of using YouTube as a learning resource to improve their English-speaking skills and the perception is influenced by internal factors and external factors from the students. The findings indicate that the students' characteristics and the features of YouTube contribute to the enhancement of English-speaking skills. However, while the majority of the students view YouTube positively as a tool for enhancing their English-speaking abilities, a minority has an opposing perspective.  Therefore, it is recommended that future research explore the long-term impact of YouTube on speaking proficiency and evaluate specific content types. Furthermore, incorporating structured YouTube-based tasks into classroom instruction may enhance learning outcomes while minimizing the challenges students face when using the platform independently.